CUTANEOUS MELANOMA – DIAGNOSIS, TREATMENT, AND THE POTENTIAL IMPACT OF PHYSICAL ACTIVITY - Izabela Lekan; Michał Lenart; Wojciech Gąska; Ignacy Rożek; Joanna Mazurek; Agnieszka Brzezińska; Weronika Tuszyńska; Alicja Sodolska; Barbara Madoń; Barbara Teresińska (International Journal of Innovative Technologies in Social Science, 2025)
Malignant melanoma is one of the most aggressive forms of skin cancer, with its incidence steadily increasing worldwide. Although it accounts for a minority of skin cancer cases, it is responsible for the majority of skin cancer–related deaths. This review discusses the epidemiology, clinical characteristics, and histopathological features of the main melanoma subtypes, including superficial spreading melanoma (SSM), nodular melanoma (NM), lentigo maligna melanoma (LMM), and acral lentiginous melanoma (ALM). Particular attention is given to current diagnostic strategies, ranging from the gold standard of histopathological examination to emerging non-invasive techniques such as dermoscopy, reflectance confocal microscopy (RCM), optical coherence tomography (OCT), high-frequency ultrasound (HFUS), and the novel tape stripping method. These approaches have improved early detection and the accurate assessment of tumor margins, supporting more personalized therapeutic planning. Treatment remains primarily surgical in early-stage melanoma, while advanced cases increasingly benefit from immunotherapy and targeted therapies, which have significantly improved survival outcomes. Additionally, this article explores the potential association between physical activity and melanoma risk, emphasizing that outdoor activity may increase susceptibility due to greater ultraviolet (UV) exposure. Prevention strategies, including public education and effective photoprotection, remain essential in mitigating disease burden. In conclusion, despite significant advances in diagnosis and therapy, malignant melanoma continues to pose major clinical and public health challenges, underscoring the importance of early detection, prevention, and ongoing research.